MANAJEMEN PELAKSANAAN PELAYANAN PUSKESMAS DI KABUPATEN JOMBANG JAWA TIMUR - Soraya Niah, Najah (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
One form of health care facilities to the public organized by the government is a publichealth center. HCF is central to the development of public health in fostering publicparticipation also provides a comprehensive and integrated services to the public. PHChas the authority and responsibility for the maintenance of public health in the workingarea. Health services provided puskesmas is comprehensive health services whichinclude services: curative (treatment), prevention (prevention), promotion (healthimprovement) and rehabilitative (health recovery). The service is addressed to allresidents, not differentiates the sexes and ages, from conception in the womb until theage cap. The formulation of the problem in this research, How to influence the planning,coordination, human resource development and performance assessment ofmanagement performance PHC?, Among the variables of planning, coordination,human resource development and performance assessment Which dominant influenceon the performance of the health center management? The method used is quantitative.The results of a study showing the planning variables have high standardized betacoefficients of the three variables To improve management of health centers need to dogood planning health center level, coordination between health centers should be carriedout human resource development and health center performance assessment. This wasdone shines the efforts that promote independence Keywords: planning, coordination,human resource development, performance assessment, performance managementclinic, Jombang